Climate Change and Development as a Bridge to Poverty in Rural Farming Communities: Best Mitigation and Adaptation Practices - Kijera, Bala Musa (European Journal of Applied Sciences, 2025)
The thesis titled Climate Change and Development as a Bridge to Poverty in Rural Farming Communities: Best Mitigation and Adaptation Practices by Bala Musa Kijera delves into the intricate relationship between climate change and sustainable development, with a specific focus on rural farming communities in the Gambia. This research identifies the main anthropogenic activities contributing to climate change and their resultant impacts on weather patterns, such as increased temperatures, altered precipitation, and severe weather events. These climatic changes pose significant challenges to agriculture, the backbone of rural livelihoods, in the Gambia in particular. Given the critical role of agriculture in sustaining rural economies and ensuring food security, the thesis underscores the urgent need for effective mitigation and adaptation strategies to address the impacts of climate change. Rural farming communities in developing countries, particularly the Gambia, are acutely vulnerable due to their reliance on agriculture with limited resources and capacities for adapting to changing climatic conditions. The research aims to identify the best practices that can enhance the resilience of these communities, thereby alleviating poverty and improving quality of life. The study highlights the importance of integrating sustainable development practices with climate resilience efforts. By adopting innovative agricultural techniques, improving resource management, and implementing policy frameworks that support climate adaptation, rural communities can better mitigate and recover from the effects of adverse weather events. The thesis draws on data such as rainfall variability and temperature fluctuations in the Gambia, demonstrating how these changes impact agricultural productivity and general environments posing existential threats to farmers' livelihoods. In conclusion, this research contributes to the global discourse on climate change and poverty alleviation by proposing actionable strategies for building resilience in vulnerable rural communities. It emphasizes the need for cohesive policies (national and international)linking climate adaptation with sustainable development goals. By fostering resilience through effective mitigation and adaptation practices, the thesis aspires to enhance the well-being and sustainable livelihoods of rural populations, ultimately bridging the gap between climate change impacts and poverty reduction.